Interaction of bleomycin, hyperthermia and a calmodulin inhibitor (trifluoperazine) in mouse tumour cells: I. In vitro cytotoxicity. - Mircheva, J. (1986)
Evidence in the literature suggests that hyperthermia (HT) or inhibitors of calmodulin can increase the sensitivity of rodent cells to bleomycin (BLM) by interfering with DNA repair functions. In an attempt to explore methods of improving the efficacy of thermochemotherapy we have investigated the individual and combined effects of HT (44 degrees C) and the calmodulin inhibitor trifluoperazine (TFP, 30 micrograms ml-1) on early plateau phase monolayer cultures of mouse EMT6 tumour cells for simultaneous exposures to BLM. Early plateau phase cultures are relatively resistant both to HT and to BLM. The selected HT and TFP regimens (either alone or in combination) were non-toxic. Comparing the sensitizing effect (given by the ratio: Do BLM/Do BLM + modifier) of the various regimens on BLM-treated cells, we found that: TFP alone had a marginal effect (ratio 1.3), HT alone showed significant potentiation (ratio 19) and the combination of HT and TFP strongly sensitized (ratio greater than 110) cells to BLM cytotoxicity. We propose that the use of calmodulin inhibitors in thermochemotherapy is worthy of further evaluation.